Construction of g-C3N4 and FeWO4 Z-scheme photocatalyst: effect of contact ways on the photocatalytic performance. Issue 33 (21st May 2018) - Wang, Cong; Wang, Guanlong; Zhang, Xiufang; Dong, Xiaoli; Ma, Chun; Zhang, Xinxin; Ma, Hongchao; Xue, Mang
Abstract : g-C3 N4 (photocatalyst I), FeWO4 (photocatalyst II) and RGO (electron media) constitutes a novel Z-scheme photocatalyst for effective RhB removal. Abstract : Photocatalysis has been regarded as an attractive strategy for the elimination of contaminants, but its performance is usually limited by the fast recombination of photogenerated electron–holes. A heterojunction photocatalyst could achieve the effective separation of electron–holes. However, the electrons migrate to the less negative band while holes move to the less positive band, leading to a weakened redox ability. Z-scheme photocatalysis is a feasible way to realize the efficient separation of photogenerated electron–holes without sacrificing the reductive ability of electrons and oxidative ability of holes. In this work, a new Z-scheme photocatalyst, composed of g-C3 N4 (photocatalyst I), FeWO4 (photocatalyst II) and RGO (electron mediator), was fabricated through a facile hydrothermal and mixing method. The effect of contact ways (the electron mediator firstly combined with photocatalyst I or with photocatalyst II) on the Z-scheme photocatalytic performance was investigated. The photocatalytic removal rate of rhodamine B (RhB) was largely enhanced by the construction of a Z-scheme photocatalyst, compared with the g-C3 N4 /FeWO4 composite without RGO. The contact ways could affect the photocatalytic ability of a Z-scheme photocatalyst. The enhanced photocatalytic performance was attributed to the Z-scheme induced efficient separation of photogenerated charge carriers. Furthermore, remaining holes (on the VB of FeWO4 ) or remaining electrons (on the CB of g-C3 N4 ) with powerful oxidation or reduction ability would promote the photocatalytic degradation of RhB.